2007
DOI: 10.17221/1888-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Orchard performance and fruit quality of 50 apple cultivars grown or tested in commercial orchards of the Czech Republic

Abstract: Tree vigour, occurrence of mildew and scab, yields, yield efficiency, fruit weight, flesh firmness and soluble solids content of apple trees on M 9 rootstock were monitored between 1998-2005 in 42 commercial orchards situated in all the major growing regions of the Czech Republic. Altogether 50 cultivars were included into the evaluation. The characteristics of newly bred or newly introduced cultivars were compared to the cultivars of standard assortment such as Gloster, Golden Delicious, Idared, Jonagold, Mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 1 publication
1
9
1
1
Order By: Relevance
“…Similar findings were reported by Kosina (2002) for Golden Delicious, Melrose and Gloster cultivars. Blažek and Hlušičková (2007) showed that the TCSA value increased with tree age, Idared cv. being lower than Melrose cv.…”
Section: Analysis Of Apple Vegetative Growth and Yieldsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar findings were reported by Kosina (2002) for Golden Delicious, Melrose and Gloster cultivars. Blažek and Hlušičková (2007) showed that the TCSA value increased with tree age, Idared cv. being lower than Melrose cv.…”
Section: Analysis Of Apple Vegetative Growth and Yieldsmentioning
confidence: 97%
“…Our research is in accordance with Torii's results showing higher yield in the B 3 and B 4 treatments with Agrozel than in the B 1 and B 2 treatments without Agrozel. Blažek and Hlušičková (2007) reported that Melrose cv. grafted on M.9 rootstock gave a higher yield as compared to Idared cv.…”
Section: Analysis Of Apple Vegetative Growth and Yieldsmentioning
confidence: 99%
“…Nutrient content in apple leaves is a feature of a specific cultivar; it is influenced, within certain limits, by the rootstocks (Ponchia et al 1997), by soil and climatic conditions (Wehunt, Purvis 1954;Blažek, Hlušičková 2007), by the phase of vegetation (Sadowski et al 1995;Weinbaum et al 2001;Holb et al 2009), and particularly by the orchard management practices, i.e. irrigation and fertilization (Hipps 1997;Nagy, Holb 2006).…”
mentioning
confidence: 99%
“…Nutrient content in apple leaves is a feature of a specific cultivar; it is influenced, within certain limits, by the rootstocks, by soil and climatic conditions (Blazek & Hlusickova, 2007), by the phase of vegetation (Holb et al, 2009), and particularly by the orchard management practices, i.e. irrigation and fertilization (Nagy & Holb, 2006;Jivan & Sal, 2014).…”
Section: Introductionmentioning
confidence: 99%